Isolation of Chlamydia trachomatis from the liver of a patient with prolonged fever. Issue 11 (November 1987) - Dan, M; Tyrrell, L D; Goldsand, G
Abstract : Chlamydia trachomatis was isolated from liver biopsy specimens on two separate occasions in a young, sexually inactive patient with a 10 month history of recurrent episodes of fever, chills, and abdominal pain. Liver function tests showed a five fold increase in alkaline phosphatase, and a 20 fold increase in 5'-nucleotidase. Liver histology changes consisted of mild inflammatory infiltrates in the portal tracts. Treatment with doxycycline was followed by complete recovery. We are not aware of any previous report describing isolation of this organism from the liver parenchyma, or of C trachomatis infection presenting as fever of obscure origin.